From awareness to accountability: strengthening pediatric antibiotic stewardship in low-resource outpatient setting - Toufeeq, Saad B.; Ahmad, Nabeel (International Journal of Contemporary Pediatrics, 2026)
In pediatric outpatient departments, antibiotic prescriptions are frequently empirical and often used for self-limiting viral illnesses, fueling antimicrobial resistance (AMR). While awareness programs have improved knowledge among clinicians and caregivers, sustainable behavioral change remains limited without accountability mechanisms. This letter highlights the critical role of pediatric antimicrobial stewardship programs (ASPs), emphasizing audit-feedback interventions that have shown up to a 23% reduction in unnecessary antibiotic initiation and a 17% reduction in broad-spectrum antibiotic selection. In low-resource outpatient settings, the lack of point-of-care diagnostics perpetuates empirical prescribing. Integrating affordable diagnostic tools, enforcing stewardship policies, and adopting the WHO AWaRe framework within regional healthcare systems can strengthen accountability and optimize antibiotic use in children.